(3GdHhQUI (B:s (3YedjGJ GdHhQUI , JfGRY GdbhGfjf , ENJUGU GdeMGce (B/s - (3jhSa jGSjf, eMeOs ((3HjQhJ(B: s (3efThYGJ GdMdHj GdMbhbjI(B, s, 2004)
(3Shb QCS GdeGd h OQGSI GdHhQUI h GdeDSSGJ GdeGdjI ef GdfGMjI GdGbJUGOjI eY fXGe GdHhQUI aj Shb GdUchc GdeGdjI h Shb GdeYGOf ZjQ GdMOjOjI h GdeYGOf GdKejfI h GdehGO GdChdjI h GdYedGJ ceG Je JfGhd JTcjd dLfI GdHhQUI h YRd CYVGFgG h UdGMjGJ dLfI GdHhQUI h CYVGFgG eY COGH GdSdhc Gdegfj ceG Je GdJWQb Gdi GdTQcGJ GdeSGgeI aj GdHhQUI , GdeUGQa GdYGedI aj dHfGf h GdeTJQchf aj GdHhQUI h cPdc egfI GdhSGWI , GdhSWGA aj GdHhQUI h eSJNOeh GdhSWGA h eDSSGJ GdhSGWI GdeGdjI eY eUOQh GdUchc GdeGdjI aj GdHhQUI h YedjGJ gPg GdGNjQI h cPdc GdUabGJ GdeHGTQI h YedjGJ GdHhQUI YHQ GdGfJQfjJ h CNjQG GdbhGfjf GdeWHbI Ydi GdHhQUI h GdGNJUGU GdbVGFj(B.s
Keywords: (3GdCShGb GdeGdjIs